Penerapan Pendekatan Pembelajaran Nazhoriyatu al-Wahdah pada Mata Pelajaran Bahasa Arab Kelas Bilingual MAN 3 Palembang - Enok Rohayati (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
This research article is motivated by differences in students' ability to understand the Arabic language learning materials while the average teachers provide learning materials using methods that are still monotonous, namely lectures so that the learning objectives have not been achieved to the fullest. Results of this study as follows: First, the application of learning approaches Naẓoriyatu Al-Wahdah has been running very well in the classroom Billingual MAN 3 Palembang in the subjects of Arabic. Second, the ability to speak Arabic bilingual class MAN 3 Palembang with both categories. Third, facts on the ground Arabic teacher can exchange thoughts in menyelesaian linguistic problems of students, and they can realize that they are a good Arabic teacher. Fourth, the obstacles in the application of learning approaches Naẓoriyatu al-Wahdah the linguistic and non-linguistic. Fifth, the factors that favor the development of Al-Wahdah Naẓoriyatu learning there are three (3) factors, namely: the environment, infrastructure and instructional media facilities.